Contributions of inshore and offshore sources of primary production to the foodweb, and the trophic connectivity between various habitats along a depth-gradient, in Sodwana Bay, Kwazulu-Natal, South Africa - Parkinson, Matthew Cameron (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2013)
Sodwana Bay, situated within the iSimangaliso Wetland Park, is ecologically important as it contains high-latitude corals and the most southerly known population of coelacanths. This thesis utilised stable isotope and lipid analyses to investigate the trophic ecology of the area, in particular, understanding the relative contribution of inshore and offshore primary production to consumers inhabiting intertidal and shallow subtidal, coral reef, deep reef, canyon head and pelagic habitats. Seaweeds, excluding certain species of red seaweeds with highly depleted carbon signatures, and phytoplankton, such as diatoms, were found to be the principal sources of primary production for all consumers. Offshore production was typified by dinoflagellates. Particulate organic matter (POM) was spatio-temporally variable. Three distinct productivity periods related to nutrient cycling were noted with enriched carbon signatures and higher organic matter loads associated with warmer water. Inshore primary production was an important source of carbon to consumers in all habitats with the exception of zooplankton that were more reliant on pelagic primary production. Benthic invertebrates reflected a gradient in the utilisation of inshore production, due to the reduced availability of this source further offshore. Consumers at the furthest sites offshore were found to include a substantial quantity of inshore-derived production in their diets. Fishes, which are more mobile, were found to incorporate a similar proportion of inshore production into their diets regardless of where they were collected from.
Keywords: Marine ecology -- South Africa -- Sodwana Bay; Food chains (Ecology) -- South Africa -- Sodwana Bay; Coastal ecology -- South Africa -- Sodwana Bay; Stable isotopes; Dinoflagellates; Marine algae